Workability and compressive strength of kenaf fiber reinforced concrete with difference water-cement ratio - Mohd Ikram, Md Yusoff (2012)
The development of civil engineering products made from natural resources are increasing worldwide, due to resources renewable issue and environmental friendly concept. Among many different types of natural resources, kenaf plants have been extensively exploited over the past few years. Therefore, this report presents an overview of the developments made in kenaf fiber reinforced concrete (KFRC), in terms of water-cement ratio and their physical properties. In this study, constant volumes of kenaf fiber are used and difference water-cement ratio (w/c) in concrete to be main focus. This study concentrated on the workability and compressive strength of KFRC compared to conventional concrete. Three tests were conducted for workability of fresh KFRC namely slump test, vebe test and compacting factor test. Meanwhile, cubes sample were subjected to compressive strength test. All of the specimens were cured in water for 7, 14 and 28 days. The result indicated that the fresh KFRC exhibit a significant increase in workability with increasing of w/c ratio in concrete mixture. However the strength of the KFRC is decreasing with increasing w/c ratio. Besides that, the strength of KFRC is lower than normal concrete. This is shows that addition of kenaf fiber in concrete did not increase the compression strength of concrete.